2017
DOI: 10.1136/bjophthalmol-2017-310186
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of the Boston type I keratoprosthesis in eyes with previous herpes simplex virus keratitis

Abstract: As greater than half of patients with unilateral HSV keratitis undergoing Kpro implantation have CDVA ≥20/50 in the contralateral eye, and as the Kpro retention failure rate in eyes with prior HSV keratitis is twice than that in eyes without prior HSV keratitis, caution should be exercised when considering Kpro implantation in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…To the best of our knowledge, there were no studies about these engineered corneal tissues regarding HSK patients except for three studies which reported the long‐term outcomes of the Boston type I Kpro in eyes with a history of HSV keratitis. The postoperative complications such as persistent epithelial defect, corneal infiltrate were approximately twice of those without HSV infection …”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…To the best of our knowledge, there were no studies about these engineered corneal tissues regarding HSK patients except for three studies which reported the long‐term outcomes of the Boston type I Kpro in eyes with a history of HSV keratitis. The postoperative complications such as persistent epithelial defect, corneal infiltrate were approximately twice of those without HSV infection …”
Section: Discussionmentioning
confidence: 97%
“…The pathogenesis of corneal graft melting is complex and infection and immune response play a key role. Previous studies have shown HSK patients undergoing LKP are at higher risk for graft failure when compared to individuals received keratoplasty for conditions such as keratoconus and Fuchs’ corneal dystrophy, which often require repeated grafting . Timely recognition and management is required to prevent the recurrence of HSV‐related inflammation and graft rejection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…44,50 Finally, Fry and colleagues reported 60% of the eyes with BCVA of 20/200 or better at 3 years in patients with herpes simplex keratitis. 48 In contrast, patients with herpes zoster infection achieved BCVA ≥20/200 only in 25% of eyes. 47…”
Section: Visual Outcomesmentioning
confidence: 97%
“…In comparison, retention in eyes with nonautoimmune forms of LSCD was better, ranging from 64% to 100% at last follow-up. 39,40,48,49,52 Of note, the two studies reporting 100% retention in chemical injury, had an incidence of KPro replacement of 10% and 22%. Interestingly, more than 70% of eyes had previous surface surgery, including limbal stem cell transplantation or mucous membrane grafting highlighting that preparation of the ocular surface in severely compromised eyes is an important step that increases keratoprosthesis success.…”
Section: Anatomical Retentionmentioning
confidence: 98%